HARDINESS PADA SINGLE MOTHER - Sirait, Nenny Yuyu Dana; Minauli, Irna (Psychology Department Faculty of Psychology Universitas Medan Area, 2015)
This study aimed to determine the hardiness on a Single Mother. This study used qualitative research. The method of collecting data using in-depth interviews. Respondents in this research were two Single Mothers. The results showed that a respondent I became a single mother for the death and respondent II for divorce. Aspect Control which is owned by a single mother in the respondents I tried to solve the financial problems intelligently and to belief in God, the respondent II resolve everything concerning the future of herself and the children. Commitment of the respondents have in common is: trying to forget her husband and live a life of its own and think about the future of children. Challenge owned by the two respondent there are any differences, namely: the respondents I assume that the challenges of living makes it learned that he is strong while the second respondent considers the challenges of life as life lessons. Factors that developing hardiness in both the respondents, namely: support for families and children, social skills in a social environment, the process of learning to life experinces, and their strong characters.Keyword :hardiness, single mother